KEKUATAN DAN SIFAT-SIFAT MEKANIK CAMPURAN PVC/CPE MENUA - Habli Masyahid (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2020)
The effect of aging on the mechanical characteristics of PVC/CPE mixtures was investigated in this study. The relationship between aging time and material properties was investigated including tensile, flexural, and hardness tests used to assess the mechanical properties. The results revealed that the PVC and CPE polymers were partially thermodynamically compatible. At the sample drop-out point, the variation between the original sample and the aged sample appears. All samples were subjected to UV test (3 types). The results of all mechanical and UV tests showed that the strength of the aged samples was reduced, but this was only a minor change.